Role of property management in service demands of elderly residents of apartment complexes - Huang, Ying-Hua; Lee, Pei-Chen (International Journal of Strategic Property Management, 2020)
An aging population results in an increased demand for services designed to meet the needs of elderly people. To enable elderly individuals to age successfully in their original residence environments, property management companies that provide services to apartment complex residents play an important role as service providers. The purpose of this study was to identify possible services that property management companies can provide to elderly residents of apartment complexes in response to changing demographics. Factor analysis was performed to identify the main areas of service demands or service demand aspects. Cluster analysis and a chi-square test were also used to identify and highlight the varied demographic characteristics and residence conditions of respondents and how they affect the level of importance attributed to each service demand aspect. Results showed seven main service aspects that were of concern to elderly individuals. Specific characteristics of elderly people that led to higher demands for certain other service aspects were also identified. The results of this study can serve as a reference for property management companies to help them provide custom design services for apartment complexes they serve and to expand their business scope and opportunities.First published online 9 October 2019